Learning from the afrocolombian cultural memory - Palacios Córdoba, Elba Mercedes; Hurtado Martínez, Omaira; Benítez Martínez, Mélida (Sociedad y Economía, 2010)
The following article exposes a standpoint about the research process which conceives the learning process of the cultural afrocolombian memory with a group of fifth grade students and their teacher, ethnoeducator, in a vallecaucan region. Here it is examined and visualized how, in ethnoeducation pedagogical processes, it is necessary to open roads and to go further than the theoretical formality already known and folklorized (from the cultural market); to go toward to the recognition of collective knowledge, rich in folkloric expressions that tell the struggle and resistance of a race, beginning with music, orality, handicraft, spirituality, games, and above all, from the voices, ignored cosmovisions which are necessary to rescue to give them their importance.